Avaliação do programa-piloto de triagem neonatal para hiperplasia adrenal congênita no estado de Minas Gerais - Isabela Leite Pezzuti (2010)
Congenital adrenal hyperplasia (CAH) is suitable for newborn screening, as it is a common and potentially fatal disease which can be easily screened by a simple hormonal measurement. Moreover, early recognition and treatment can prevent severe salt wasting, reducing morbidity and mortality. The aim of this study was to evaluate the neonatal screening program for CAH established in the state of Minas Gerais, as a pilot project, between 09/01/2007 and 05/01/2008. Screening for CAH was included in the Newborn Screening Program of the State of Minas Gerais (PETN-MG), which covers 100% of the municipalities of the state and routinely conducts research on four diseases (phenylketonuria, congenital hypothyroidism, hemoglobinopathies and cystic fibrosis). Heel-puncture blood samples are collected on filter paper on day fifth after birth. Dried blood samples were analyzed for 17-OHP by UMELISA 17OH Progesterona Neonatal® assay. Normal range was established at 80 nmol/L. Since 11/29/2007 it was adopted a specific cut-off for children with birth weight less than 2,500g or preterm (160 nmol/L). A total of 159,415 children were screened. The incidence for the classic form of the disease was 1:19,927. Among the eight children detected (five females), six had the salt wasting form of the disease. Four children were clinically unsuspected and diagnosis was entirely attributable to neonatal screening. Therapy was started at a median age of 39 days. The median 17-OHP on filter paper of affected children was 250 nmol/L and of false-positive children was 132 nmol/L (P <0.001). False-positive rate was 0.31% and PPV was 2.1%. The sensitivity and specificity were 100 and 99.7%, respectively. Among the 315 falsepositive children followed by PETN-MG, 62% were male, 76% had history of perinatal complications and 63% were premature and/or had low birth weight. The follow-up of false-positive children was long (median of 17 months of life at discharge), and the median time to normalization of serum 17-OHP levels (13.5 months) were significantly higher than that of serum androstenedione (3.3 months; p <0.001). Forty-eight false-positive children (15%) were still under clinical observation at 07/20/2010, with age of 24 6 months in last evaluation. Median 17-OHP values on filter paper were inversely related to birth weight in screened population (p <0.001). The use of new cut-offs, based on 99th percentile of 17-OHP according to 4 birth weight groups (>= 2,500g; 2,000-2,499g, 1,500- 1,999g and <1,500g), would lead to a reduction in 82% of the false-positive rate without loss of sensitivity and a 5-fold increase in PPV. The findings - relatively high incidence of the disease with the prospect of significant reduction in morbidity and mortality - justify the implementation of neonatal screening for CAH in the state of Minas Gerais. The parameters obtained as good sensitivity and specificity of the test with the prospect of reducing false-positive rate and improving PPV, demonstrate the feasibility of neonatal screening and the possibility of establishing a cost-effectiveness program.